The impact of overhead dumbbell squat towards swimming speed of Tirta Palm Swimming Club members - Winaspita Aulia Putri; Adelia Handoko; Ulfa Elfiah (Jurnal Keolahragaan, 2022)
Swimming athletes compete by how fast they can swim at a certain distance. One of the most important things that affect the swimming speed was the muscle strength of the arms and legs. The swimming speed can be increased by doing the physical exercise that can affect the arms and legs muscles which was called overhead dumbbell squat (ODS) exercise. The purpose of this study was to find out if there was an effect of ODS on increased breaststroke swimming speed of Tirta Palm Swimming Club members. This study was an experimental study with one group pretest-posttest design that was implemented for a month about 16-20 years old that met the qualifications of inclusion and did the ODS exercise thrice a week for 4 weeks. The duration of each exercise was 10 repetitions, 6 sets, and breaks for a minute in each set. The result showed that the average pretest swimming speed was 67,84 seconds and the post-test was 59,07 seconds. The analysis result of paired sample t-test showed a value p0,001, so there was a significant difference between pretest and posttest. It could be concluded that overhead dumbbell squat exercises could enhance the swimming speed of Tirta Palm Swimming Club members.